2006
DOI: 10.1016/j.jmaa.2005.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on global existence for the supercritical nonlinear Schrödinger equation with a harmonic potential

Abstract: This paper is concerned with the nonlinear Schrödinger equation with a harmonic potential which describes the attractive Bose-Einstein condensate under the magnetic trap. By combining the best constant of Gagliardo-Nirenberg's inequality with the characteristic of this equation, we derive out a global existence condition for the supercritical equation which coincides with the critical case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…3) in the case of supercritical nonlinearity 1 + (4 + 2b)/N < p <p. An interesting aspect is that we can get the global solutions for arbitrarily large data. We will use Theorem 1.1 and some ideas from [2,20], which was used in [6]. We emphasize that the use of Theorem 1.1 is essential.…”
Section: Critical Mass On the Existence Of Global Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) in the case of supercritical nonlinearity 1 + (4 + 2b)/N < p <p. An interesting aspect is that we can get the global solutions for arbitrarily large data. We will use Theorem 1.1 and some ideas from [2,20], which was used in [6]. We emphasize that the use of Theorem 1.1 is essential.…”
Section: Critical Mass On the Existence Of Global Solutionsmentioning
confidence: 99%
“…Remark 1.2 When K (x) = 1, Fukuizumi [9] , Rose and Weinstein [14] and Zhang [6,23] obtained some results of the stability and instability of standing waves as well as global existence of (1.2) for various initial profiles. It is observed that there is a basic estimate used in their papers, i.e.…”
mentioning
confidence: 99%
“…And under what conditions, will the condensates exist for all time (global existence)? Especially the sharp criteria of blowing up and global existence are pursued strongly(also see [7,8,9,23,25,26]). From the view point of mathematics, the problems are rather fascinating and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Zhang [13] derived a global existence condition for the supercritical case for (3), which coincides with the critical case. For (4), Fujiwara [14] proved that the smoothness of the Schrödinger kernel for potentials of quadratic growth.…”
Section: Introductionmentioning
confidence: 77%